Problematics Faced by Elementary School Teachers in Integrating Differentiated Learning within the Merdeka Curriculum: Problematika Guru SD dalam Mengintegrasikan Pembelajaran Berdiferensiasi Kurikulum Merdeka - Putri Indah Wahyuningsih; Rahayu Pristiwati; Putri Indah Wahyuningsih; Rahayu Pristiwati (Jurnal Riset Madrasah Ibtidaiyah, 2026)
The implementation of the Merdeka Curriculum requires elementary school teachers to apply differentiated instruction in order to accommodate students’ diverse learning needs and characteristics. However, in practice, teachers continue to encounter various challenges in integrating this approach. This study aims to describe the challenges faced by elementary school teachers in implementing differentiated learning within the Merdeka Curriculum. A qualitative case study method was employed, with third-grade teachers at SD Negeri 02 Pedes, Bantul, Yogyakarta, serving as the research subjects. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing and verification. The findings indicate that teachers have made efforts to implement differentiated learning through content, process, and product differentiation based on diagnostic assessments. Nevertheless, teachers still experience difficulties, including limited understanding of the concept of differentiated learning, diversity in students’ abilities and characteristics, insufficient training and institutional support, limited use of technology, as well as time constraints and administrative workload. These findings suggest that the successful implementation of differentiated learning requires sustained support in the form of enhanced teacher competence, targeted professional development, and the provision of adequate facilities and infrastructure to ensure the optimal and inclusive achievement of the Merdeka Curriculum objectives.